Identification of genomic regions required for DNA replication during Drosophila embryogenesis. - Smith, A.V.; King, J.A.; Orr-Weaver, T.L. (Genetics, 1993)
A collection of Drosophila deficiency stocks was examined by bromodeoxyuridine (BrdU) labeling of embryos to analyze the DNA replication patterns in late embryogenesis. This permitted us to screen 34% of the genome for genes that when absent in homozygous deficiencies affect the cell cycle or DNA replication. We found three genomic intervals that when deleted result in cessation of DNA replication in the embryo, 39D2-3;E2-F1, 51E and 75C5-7;F1. Embryos deleted for the 75C5-7;F1 region stop DNA replication at the time in embryogenesis when a G1 phase is added to the mitotic cell cycle and the larval tissues begin to become polytene. Thus, this interval may contain a gene controlling these cell cycle transitions. DNA replication arrests earlier in embryos homozygous for deletions for the other two regions. Analysis of the effects of deletions in the 39D2-3;E2-F1 region on DNA replication showed that the block to DNA replication correlates with deletion of the histone genes. We were able to identify a single, lethal complementation group in 51E, l(2)51Ec, that is responsible for the cessation of replication observed in this interval. Deficiencies that removed one of the Drosophila cdc2 genes and the cyclin A gene had no effect on replication during embryogenesis. Additionally, our analysis identified a gene, pimples, that is required for the proper completion of mitosis in the post-blastoderm divisions of the embryo.